Unusual viscosity behavior of polyacrylonitrile in NaSCN aqueous solutions. (1st May 2015) - Xu, Li; Qiu, Feng
Abstract: The rheological behaviors of polyacrylonitrile (PAN) and its copolymers in various NaSCN aqueous solutions are investigated. An unusual shear-viscosity behavior that is unique for PAN/NaSCN aqueous solutions is identified: both in the high and low NaSCN concentration ( C NaSCN ) regimes, the PAN solution viscosities are higher, with the minimum occurring at C NaSCN  = 48–50 wt% for the 11wt% PAN solutions. Infrared spectroscopic and dynamic light scattering measurements are employed to elucidate the solution-structural changes that are responsible for this unusual viscosity behavior. Accordingly, a tentative dissolution mechanism in PAN solutions with high C NaSCN and gelation mechanism with low C NaSCN are proposed. Graphical abstract: Highlights: The unusual η - C NaSCN curve for PAN/NaSCN aqueous solutions is investigated. Rheological studies reveal the fluid and gel states exist for PAN aqueous solutions with different C NaSCN . IR and DSL measurements are employed to elucidate the unusual viscosity behavior. Three kinds of chain conformations of swelling, collapse and association are tentatively proposed.